Giant clumps in simulated high-z galaxies: properties, evolution and dependence on feedback - Mandelker, Nir; Ceverino, Daniel (Monthly notices of the Royal Astronomical Society, 2016)
We study the evolution and properties of giant clumps in high-z disc galaxies using adaptive mesh refinement cosmological simulations at redshifts z ∼ 6-1. Our sample consists of 34 galaxies, of halo masses 1011-1012 M⊙ at z = 2, run with and without radiation pressure (RP) feedback from young stars. While RP has little effect on the sizes and global stability of discs, it reduces the amount of star-forming gas by a factor of ∼2, leading to a similar decrease in stellar mass by z ∼ 2. Both samples undergo extended periods of violent disc instability continuously forming giant clumps of masses 107-109 M⊙ at a similar rate, though RP significantly reduces the number of long-lived clumps (LLCs). When RP is (not) included, clumps with circular velocity ≲ 40 (20) km s− 1, baryonic surface density ≲ 200 (100)M⊙ pc− 2 and baryonic mass ≲ 108.2 (107.3) M⊙ are short-lived, disrupted in a few free-fall times. More massive and dense clumps survive and migrate towards the disc centre over a few disc orbital times. In the RP simulations, the distribution of clump masses and star formation rates (SFRs) normalized to their host disc is similar at all redshifts, exhibiting a truncated power law with a slope slightly shallower than −2. The specific SFR (sSFR) of the LLCs declines with age as they migrate towards the disc centre, producing gradients in mass, stellar age, gas fraction, sSFR and metallicity that distinguish them from the short-lived clumps which tend to populate the outer disc. Ex situ mergers comprise ∼37 per cent of the mass in clumps and ∼29 per cent of the SFR. They are more massive and with older stellar ages than the in situ clumps, especially near the disc edge. Roughly half the galaxies at redshifts z = 4-1 are clumpy, with ∼3-30 per cent of their SFR and ∼0.1-3 per cent of their stellar mass in clumps.
Gesehen am 26.10.2017